The Influence of Learning Motivation, Discipline, and Time Management on the Academic Achievement of Students in the Faculty of Economics at Universitas Negeri Jakarta - Muhamad Aqdi Alhamro; Osly Usman, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Academic achievement is the result of learning obtained through cognitive educational activities, measured through evaluation and assessment. This study explores the influence of learning motivation, discipline, and time management on the academic achievement of students in the Faculty of Economics at Universitas Negeri Jakarta. Using a qualitative approach, data from 100 students in the Faculty of Economics at Universitas Negeri Jakarta were analyzed with Structural Equation Modeling Partial Least Squares (SEM-PLS). The findings show that discipline has a significant effect on time management (p-value = 0.000), and learning motivation also significantly affects time management (p-value = 0.001). Time management was found to have a direct and significant impact on academic achievement (p-value = 0.014). Learning motivation (p-value = 0.044) and discipline (p-value = 0.037) also have significant direct effects on academic achievement. Additionally, it was found that discipline has a positive indirect effect on academic achievement through time management (p-value = 0.032), while learning motivation does not have a significant indirect effect on academic achievement through time management (p-value = 0.059). These findings emphasize the importance of enhancing motivation, discipline, and time management among students to achieve optimal academic performance.